Implications of Women leadership development with respect to Feminism - Toheed, Hira Toheed (Advances in Social Sciences Research Journal, 2019)
This paper is anticipated to examine the role of global feminism and gender stereotype behavior on women’s leadership development. Moreover, the present research is accentuating to shed light on how global feminism and gender stereotypes have affected the female employees work life generally, and leaders especially. This study is aimed to analyze the current status of women’s leadership development, and to investigate how to improve it in future. Women have always been an unsung hero of the society and stereotyping hinders women’s career progression over the globe. The study selected 15 female leaders from various sectors, I.E, (education, media, medical, and NGOs) from Islamabad. The present study followed the inductive research approach through semi-structure interviews. The study divulges that leadership does not confine in the cage of gender stereotyping. The study shows that it is right time to remove such barriers from the society giving everyone equal opportunity to lead and achieve outstanding organizational performance. The study has significant implications towards mainstreaming women leaders in every walk of life. This research will enhance the digging of knowledge, skills and wisdom in women generally and of Pakistani women specifically.